Network analysis of 18 attention-deficit/hyperactivity disorder symptoms suggests the importance of “Distracted” and “Fidget” as central symptoms: Invariance across age, gender, and subtype presentations - Liu, Lu; Wang, Yi; Chen, Wai; Gao, Yuan; Li, Haimei; Wang, Yufeng; Chan, Raymond C. K.; Qian, Qiujin (Frontiers in Psychiatry, 2022)
The network theory of mental disorders conceptualizes psychiatric symptoms as networks of symptoms that causally interact with each other. Our present study aimed to explore the symptomatic structure in children with ADHD using network analyses. Symptom network based on 18 items of ADHD Rating Scale-IV was evaluated in 4,033 children and adolescents with ADHD. The importance of nodes was evaluated quantitatively by examining centrality indices, including Strength, Betweenness and Closeness, as well as Predictability and Expected Influence (EI). In addition, we compared the network structure across different subgroups, as characterized by ADHD subtypes, gender and age groups to evaluate its invariance. A three-factor-community structure was identified including inattentive, hyperactive and impulsive clusters. For the centrality indices, the nodes of ‘Distracted’ and ‘Fidget’ showed high closeness and betweenness, and represented a bridge linking the inattentive and hyperactive/impulsive domains. ‘Details’ and ‘Fidget’ were the most common endorsed symptoms in inattentive and hyperactive/impulsive domains respectively. On the contrary, the ‘Listen’ item formed a peripheral node showing weak links with all other items within the inattentive cluster, and the ‘Loss’ item as the least central node by all measures of centrality and with low predictability value. The network structure was relatively invariant across gender, age and ADHD subtypes/presentations. The 18 items of ADHD core symptoms appear not equivalent and interchangeable. ‘Distracted’ and ‘Fidget’ should be considered as central, or core, symptoms for further evaluation and intervention. The network-informed differentiation of these symptoms has the potentials to refine the phenotype and reduce heterogeneity.